2005
DOI: 10.1029/2004jb003485
|View full text |Cite
|
Sign up to set email alerts
|

Ferrimagnetic resonance signal produced by frictional heating: A new indicator of paleoseismicity

Abstract: High‐speed fault slips during earthquakes may generate sufficient frictional heat to produce fused fault rocks such as pseudotachylyte. We have carried out high‐speed slip tests using natural fault gouge to judge whether or not frictional heating universally occurs during seismic fault slips. In our shearing tests, natural fault gouge is put between two cylindrical silica glasses and sheared under a fixed axial stress of 0.61 MPa. Despite such a low stress near the Earth's surface, a darkened cohesive material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 36 publications
0
41
0
1
Order By: Relevance
“…A number of reactions, driven by frictional heating, may account for the observed increases of magnetic susceptibility in fault rocks. Two examples of such reactions are: (R 1 ) siderite ⇒ pyrite or pyrrhotite ⇒ magnetite, under low oxygen fugacity [ f O 2 ] (Chelungpu Fault [Tanikawa et al, 2008]); (R 2 ) goethite ⇒ hematite, under higher f O 2 (Nojima Fault [Fukuchi et al, 2005] Fukuchi, 2003;Petrík et al, 2003]. However, other factors such as host rock composition and degree of melting also affect f O 2 and thus the magnetic properties of pseudotachylytes [Henkel and Reimold, 2002;Nakamura and Iyeda, 2005;Zechmeister, 2005;Hirono et al, 2006].…”
Section: Importance Of Variations In Magnetic Susceptibility In Faultmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of reactions, driven by frictional heating, may account for the observed increases of magnetic susceptibility in fault rocks. Two examples of such reactions are: (R 1 ) siderite ⇒ pyrite or pyrrhotite ⇒ magnetite, under low oxygen fugacity [ f O 2 ] (Chelungpu Fault [Tanikawa et al, 2008]); (R 2 ) goethite ⇒ hematite, under higher f O 2 (Nojima Fault [Fukuchi et al, 2005] Fukuchi, 2003;Petrík et al, 2003]. However, other factors such as host rock composition and degree of melting also affect f O 2 and thus the magnetic properties of pseudotachylytes [Henkel and Reimold, 2002;Nakamura and Iyeda, 2005;Zechmeister, 2005;Hirono et al, 2006].…”
Section: Importance Of Variations In Magnetic Susceptibility In Faultmentioning
confidence: 99%
“…These mid-Proterozoic and Caledonian veins, from a few millimeters up to several meters thick, reveal a strong remanent magnetization (Q ratios = 10 to 100), carried by single domain (SD) to pseudo-single domain (PSD) magnetite grains. Fukuchi [2003] and Fukuchi et al [2005] studied pseudotachylytes from the Nojima Fault, Japan, responsible for the devastating 1995 Kobe earthquake (M = 7.2). These veins originated from cataclasis and not from frictional melting [Lin, 2001].…”
Section: Natural Pseudotachylytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ferrimagnetic minerals commonly show huge ESR absorption due to their spontaneous magnetization, we can detect them as FMR (ferrimagnetic resonance) signals using the ESR technique. Detailed ESR analyses showed that the growth process of FMR signals during heating may fundamentally follow the zero-order reaction kinetics (Fukuchi, 2003;Fukuchi et al, 2005). Therefore, we can use FMR signals as an effective index of frictional heat.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we had required any new technique to directly estimate frictional heat from fault rocks. Recent ESR (electron spin resonance) and magnetic studies of fault zones revealed that fault rocks may have been magnetized due to the thermal decomposition of iron-bearing paramagnetic or antiferromagentic minerals included in host rocks into ferrimagnetic ones by frictional heating (Fukuchi, 2003;Fukuchi et al, 2005Fukuchi et al, , 2007Ferré et al, 2005;Han et al, 2007). Since ferrimagnetic minerals commonly show huge ESR absorption due to their spontaneous magnetization, we can detect them as FMR (ferrimagnetic resonance) signals using the ESR technique.…”
Section: Introductionmentioning
confidence: 99%